Analisis Kepemimpinan Ketua Pondok dalam Revitalisasi Etos Kerja Kepengurusan PPM Al-Husna 2 - Fatimatuz Zahro; Yang Fainy Wigiart Nindya Putri; Lailatul Ussriya; Aniqotuzzuhro' Fitriana (Medan Resource Center, 2023)
Al Husna 2 Student Islamic Boarding School (PPM) is a place for students who continue their education at the college level, commonly called mahasantri. PPM Al Husna 2 is a branch of PPM Al Husna 1, therefore the caregiver gives full responsibility to the board of the boarding school. The chairman of the hut here is very influential on the progress of the hut. To carry out developments and advance the PPM Al Husna cottage chairman is currently revitalizing programs that did not exist in the previous management. This journal aims to determine the leadership exercised by the head of the Islamic boarding school in revitalizing the work ethic of the administrators at PPM Al Husna 2. Qualitative research is a method used by researchers in their research with a sociological-anthropological approach, namely being directly involved in activities in the Islamic boarding school. . By obtaining descriptive data in the form of oral or written from one of the respondents, with a total population of 12 responses, ie 7 from administrators and 5 from students. So, the data obtained is in the form of words, pictures, and not numbers. So the results of this study are that the head of the boarding school himself has a strategy in revitalizing his work ethic, as well as the work ethic of the students at the boarding school so that the formation of the existing work ethic in the boarding school can shape the students to have responsibility, encourage the students to develop their knowledge and skills, and can be a value that is attached to the students themselves.